Sound Practice—improving occupational health and safety for professional orchestral musicians in Australia - Ackermann, Bronwen J.; Kenny, Dianna T.; O'Brien, Ian; Driscoll, Tim R. (Frontiers in Psychology, 2014)
The Sound Practice Project is a five-year study involving baseline evaluation, development and implementation of musician-specific work health and safety initiatives. A cross-sectional population physical and psychological survey and physical assessment were conducted at the same time, with an auditory health assessment conducted later. The results were used to guide the development of a series of targeted interventions, encompassing physical, psychological and auditory health components. This paper provides an overview of the project but focuses on the health findings arising from the cross-sectional survey. 377 musicians from the eight professional symphony orchestras in Australia took part in the cross-sectional study (about 70% of eligible musicians). Eighty-four percent (84%) of musicians reported past performance-related musculoskeletal disorder (PRMD) episodes; 50% were suffering a current PRMD. Of the 63% who returned hearing surveys, 43% believed they had hearing loss, and 64% used earplugs at least intermittently. Noise exposure was found to be high in private practice, although awareness of risk and earplug use in this environment was lower than in orchestral settings. Improved strategic approaches, acoustic screens and recently developed active earplugs were found to provide effective new options for hearing protection. With respect to psychosocial screening, female musicians reported significantly more trait anxiety, music performance anxiety, social anxiety, and other forms of anxiety and depression than male musicians. The youngest musicians were significantly more anxious compared with the oldest musicians. Thirty-three percent (33%) of musicians may meet criteria for a diagnosis of social phobia; 32% returned a positive depression screen and 22% for post-traumatic stress disorder. PRMDs and trigger point discomfort levels were strongly associated with increasing severity of psychological issues such as depression and music performance anxiety.